Declining T-cell immunity to influenza, 1977-82. - Mcmichael, A; Gotch, F; Dongworth, D; Clark, A; Potter, C (1983)
Influenza-A-virus-specific, HLA-restricted, cytotoxic T-cell immunity, measured in 189 volunteers in the six years 1977-82, showed a sharp decline from 1978. It is shown that natural infection with influenza-A virus boosts cytotoxic T-cell memory. The decline in T-cell immunity is probably associated with the low prevalence of influenza-A-virus infection since 1978.